Recuperação seletiva de índio a partir da técnica de extração em fase sólida utilizando nanofibras com DEHPA - Cadore, Jéssica Stefanello (2019)
The main objective of this work was to develop a nanomaterial able to selectively extract and recover indium (In) from obsolete cell phone LCD screens. For this, Nylon 6 nanofibers were produced and modified with di-(2-ethylhexyl)phosphoric acid (DEHPA) for application in the solid-phase extraction of In. The best extraction conditions for concentration of In were 30% DEHPA, pH 0.5, 7.5 min contact time, and S:L ratio of 1:300. In this step, an In extraction efficiency of around 74% was obtained. In stripping steps, an efficiency of 92% was achieved using 1.5 M HCl, S:L ratio of 1:20, and 5 min contact time. Under the best extraction and stripping conditions, it was possible to obtain up to 6-fold concentration of In, compared to the initial concentration. In addition, the nanofibers were evaluated in terms of their stability and capacity for reuse, which showed that there was no significant loss of DEHPA and that the extraction efficiency remained almost constant. The findings demonstrated the possibility of using the Nylon 6/DEHPA nanofibers in a highly efficient extraction/stripping procedure for the selective recovery of In and Sn, with reduced environmental impacts.